Thermodynamic response of gas injection-and-withdrawal process in salt cavern for underground gas storage. (25th December 2019) - Li, Wenjing; Zhu, Cheng; Han, Juan; Yang, Chunhe
Highlights: Analytical solution to temperature and pressure variation in gas injection-and-withdrawal process was derived. The mathematical model is employed to calculate the thermal stress. Fully coupled thermal-mechanical numerical simulations are performed. Fast gas-withdrawal rate induces more tensile stress concentrations. Abstract: Cycled mode of operation leads to temperature and pressure variation in salt cavern for underground gas storage due to mechanical and thermal loading. In this study, based on metamorphic thermodynamic principle, a mathematical model of thermal analysis is proposed for gas injection-and-withdrawal process, formulates a newly analytical solution to temperature and pressure variation with time during injection-and-withdrawal process. The proposed solution is validated with the withdrawal test results. The derived solution can be set as boundary conditions for the thermal-mechanical numerical modeling, which is capable of calculating thermodynamic response for both constant and in-constant air mass flow rate. Fully coupled thermo-mechanical numerical simulations are preformed to evaluate thermal effects on cavern wall at different gas withdrawal and injection rates. The results indicate that during process of gas-withdrawal, fast withdrawal rate leads to increase of tensile stresses, and there are distinctive tensile stress areas on the roof and floor of the cavern; while in the gas-injection period, there are no tensile stress area, however, it inclines to occur stress disturbance at intervention of interlayers. Parameters analysis shows that both the thermal coefficients and variation of injection-and-withdrawal rates have impacts on the thermodynamic responses of surrounding rock mass.